The Effect of Asset Structure, Capital Structure, and Company Size on Stock Prices With Profitability as an Intervening Variable in Multi-Industry Sector Companies Listed on the Indonesia Stock Exchange in 2018 - 2021 - Alexsius Laurenzo Talaud; Nekky Rahmiyati (Best Journal of Administration and Management, 2023)
This study aims to analyze the effect of asset structure, capital structure and company size on stock prices with profitability as an intervening variable in various industrial companies for the 2018-2021 period. The method used in this study uses quantitative data by collecting data in the form of annual financial reports for the 2018-2021 period with a total sample of 9 companies listed on the Indonesia Stock Exchange. The analysis technique used is outer model analysis, inner model analysis and hypothesis testing. Data processing uses Smart PLS 3.0. The results of this study indicate that asset structure does not have a significant effect on stock prices, asset structure does not have a significant effect on profitability, capital structure does not have a significant effect on stock prices, capital structure does not have a significant effect on profitability, company size does not have a significant effect on stock prices, company size has a significant effect on profitability and profitability has no significant effect on stock prices in various industrial companies listed on the IDX for the 2018-2021 period.